Il disagio del piacere. Effetti di lettura in "Se una notte d’inverno un viaggiatore" di Italo Calvino (ENTHYMEMA, 2020)
The reader’s novel presents itself as an ‘inventory of effects’ of the reading activity, represented through different reading styles (in particular in the frame story) or through the simulation of reading experiences, as in the ten incipits of the novels within the novel. Moreover, the ‘inventory of effects’ is represented through a plurality of literary genres, and especially through a number of mental-sensitive experiences, that is, of the various forms in which the emotional-rational involvement of the reader in constructing fictional worlds takes place. The sort of experience that If on a Winter’s Night a Traveler offers its real readers revolves around a system of binary tensions (protagonism/dispossession, immersion/detachment, embodiedness/ fading out), in alternating balance. Calvino creates an ambivalent aesthetic object, markedly ambiguous, which can be the source of an irritating and unsatisfactorily pleasure. At the end of the novel, the reader feels a sense of both uneasiness and pleasure, experiencing the potential as well as the limits of the literary expression.
Keywords: Italo Calvino; If on a Winter’s Night a Traveler; reading styles; emotions; identification